Vascular cell signaling by membrane estrogen receptors - Bender, Jeffrey (Henry Stewart Talks, 2007)
Endothelium, Endothelial dysfunction, Estrogen-mediated cardiovascular protection and leukocyte-endothelial cell adhesion, Estrogen as a determinant of cardiovascular risk, Effects of estrogen on the cardiovascular system, Rapid EC activation effects of estrogen, Effect of estradiol on NO release from human endothelial cells, Estrogen receptor knockout (ERKO) mouse cardiovascular studies, Palmitoylation is required for membrane translocation of ER46, Akt/protein kinase B, Endothelial homeostasis, Kronos early estrogen prevention study